Comparing recent Danish, Finnish and Swedish labour market policy reforms - Robert Arnkil; Timo Spangar (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
The goal of this first report of the 'Benchmarking Employment Offices - Nordic and Other European Comparisons (acronym BEO) is an analytical comparison of the Danish, Finnish and Swedish labour market policy principles and structures primarily from a practical point of view. The purpose is to provide a background to compare, at a later stage, the recent reforms in the labour administrations in the Nordic countries (including later also Norway) with Germany and Holland. In reflecting on the Danish, Finnish and Swedish labour market policy and service reforms, we mainly use the Danish reform as a reference point, and then comment on the similarities and differences of Finland and Sweden in relation to it. It must be noted, however, that the Swedish observations are based on a preliminary study, and will be elaborated further as our work progresses. – – Das Ziel dieses ersten Berichts des Projekts 'Benchmarking von Arbeitsämtern - nordeuropäische und andere europäische Vergleiche' ist ein - pragmatischer - analytischer Vergleich der Prinzipien und Strukturen der dänischen, finnischen und schwedischen Arbeitsmarktpolitik und ihrer Strukturen. Damit soll eine Art 'Folie' für spätere Vergleiche der kürzlich durchgeführten Reformen in den Arbeitsverwaltungen der nordeuropäischen Ländern inkl. Norwegens mit denen in Deutschland und Holland geschaffen werden. Für die Analyse der dänischen, finnischen und schwedischen Arbeitsmarktpolitik und Reformen der Arbeitsverwaltung wird hauptsächlich die dänische Reform als Referenzrahmen verwendet. Unter Bezug darauf werden Ähnlichkeiten und Unterschiede für die Fälle Finnland und Schweden beschrieben und kommentiert. Für den Fall Schweden muß allerdings darauf hingewiesen werden, daß die Ergebnisse auf einer vorläufigen Studie beruhen und in einem späteren Arbeitsschritt weiter ausgearbeitet werden.
Keywords: 330; Arbeitsmarktpolitik; Arbeitsverwaltung; Reform; Vergleich; Dänemark; Finnland; Schweden